2021
DOI: 10.1111/jog.14682
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ascites volume and clinical outcomes in epithelial ovarian cancer

Abstract: Objective Ascites is a tumor microenvironment, ascites and massive ascites‐induce compression could promote the progression of epithelial ovarian cancer (EOC); however, the impact of ascites volume on clinical outcomes has not been studied extensively. We aimed to investigate the association between ascites volume and clinical outcomes especially platinum resistance in EOC. Methods We retrospectively evaluated a total of 546 EOC patients with respect to the amount of ascites, clinicopathologic factors, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Malignant ascites frequently develops in women with HGSOC ( 4 , 19 ). The composition of T-cell subsets in ascites is associated with drug resistance and a poor prognosis ( 5 , 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Malignant ascites frequently develops in women with HGSOC ( 4 , 19 ). The composition of T-cell subsets in ascites is associated with drug resistance and a poor prognosis ( 5 , 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…More investigation for an adequate method to evaluate patients with this metabolic pattern is needed. In any case, the impact of ascites volume on ovarian cancer outcome has been already studied, nding that it is an independent factor correlated with shorter PFS, suboptimal cytoreduction and chemoresistance [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…We included age, NACT, residual tumor, volume of ascites, LNM, CA125, FIGO stage, location of primary tumor, and diameter of primary tumor as clinical features. Previous study indicated the volume of ascites was an independent predictor of PFS and OS in patients with epithelial ovarian carcinoma (24,25). Although in previous study the threshold of volume was set to 1500 ml or 2000 ml respectively to classify patients into small-and large-volume ascites groups.…”
Section: Discussionmentioning
confidence: 99%